Non-syndromic Cleft Lip and Palate Polymorphisms Affect Normal Lip Morphology - Wilson-Nagrani, Caryl; Richmond, Stephen; Paternoster, Lavinia (Frontiers in Genetics, 2018)
Non-syndromic cleft lip with or without palate (NSCL/P) is a frequent malformation of the facial region. Genetic variants (SNPs) within nineteen loci have been previously associated with NSCL/P in GWAS studies of European individuals. These common variant SNPs may have subtler effects on the morphology of the lip and face in unaffected individuals. Several studies have investigated the genetic influences on facial morphology using land-marking methods, but these landmarks are sparse in the lip region. The aim of this study is to assess for associations between the nineteen NSCL/P SNPs and normal lip phenotypes, using a detailed categorical scale. Three-dimensional laser scanned facial images were obtained of 4,747 subjects recruited from the Avon Longitudinal Study of Parents and Children (ALSPAC) and genetic data was available for 3,643 of them. A polygenetic risk score (PRS) combining the nineteen NSCL/P SNPs was associated with V-shaped Cupid’s bow (P=3x10-4) and narrow philtrum (P=2x10-4) phenotypes. Analysis of individual SNPs found strong evidence for association between rs227731 and skeletal II pattern (P=5x10-6). This study finds that known NSCL/P SNPs affect lip phenotypes in the general population, and an increased PRS is associated with narrow philtrum and V-shaped Cupid’s bow. However, the difference in NSCL/P PRS between people with and without certain lip features is unlikely to be great enough to serve as a useful marker of NSCL/P risk.